Communication Skills And Perceived Stress of Nursing Students During First Clinical Experience - Gül Güneş AKTAN; Leyla KHORSHID (Atatürk University, 2021)
Aim: To evaluate the relationship between communication skills and perceived stress of nursing students during the first clinical experience. Methods: The cross-sectional descriptive study was conducted with 225 nursing students over the period of February 2018 and June 2018. The students compared the following criteria: willing to participate in the study, being in first clinical experience. The Communication Skills Scale, the Perceived Stress Scale, and the Individual Identification Form were used for collecting data. Findings: It showed that nursing students' level of communication skills was high and the level of perceived stress was moderate. There was a weak positive correlation between nursing students' communication skills and perceived stress. Conclusion: Considering that the stress level of students is moderate and the communication skills level is high, this result can be considered as a positive outcome. Effective communication skills are needed to minimize the high stress experienced in clinical practice.